Manejo de los desechos orgánicos producidos en el mercado San Francisco, cantón Joya de los Sachas, provincia de Orellana - Cedeño Centeno, Lely Darwin (2016)
This research project "Management of organic waste produced on the market San Francisco, Canton La Joya de los Sachas" was held in the market San Francisco, Orellana Province, the administration of Mercado San Francisco has no data on amount of waste ripe fruit, vegetables and legumes that are generated in it, which is why it became necessary to do research and make the use of waste for the production of organic fertilizer being an ecological agricultural alternative that provides nutrients for the development of plants, while contributing to reduce the volume of organic solid waste going to landfill. The objectives were to characterize organic waste in the San Francisco market, for the production of organic fertilizers, develop a proposal for the use of organic waste, share the results with traders at the headquarters of the San Francisco market. descriptive, deductive, inductive and analytical: Regarding methodology methods were used. As it regards the variables to evaluate: Characterization of waste to produce fertilizer types, economic analysis, dissemination of results. The results indicate that among the main weaknesses existing in the San Francisco market is the lack of planning regarding the distribution of commercial premises, inadequate waste classification. The waste produced are mostly organic, the problem is not identifying waste, ie what type of waste is part as organic and inorganic. It shows. a proposal for the Retail Merchants Association (market) San Francisco, Canton Joya de los Sachas, is proposed in order to establish a firm organic fertilizers quality that contribute to plant nutrition, health and soil fertility as well as improving the environment by recycling organic solid waste conditions. The company AgrOrganic Joya de los Sachas S.A., will on his land of 640 m2 initially with 9 beds (20 m x 1 m = 20 m2) for the production of vermicompost. Annually for each bed of 20 m2 you are obtained 10.8 tons of humus, equivalent to the first year of production 97.20 TM or 2,160 bags of 45 kg c / u final, Humus product. Product costs increase as the production increases, starting from year one with a cost of $ 48,536 USD with an initial production of 2,160 bags of 45 kg c / u. ($ 4,045.00 monthly) taking into account that in this first phase investment cost is $ 20,000. For the fifth year, the cost of production according to the projection a total cost of $ 68,804.00 USD ($ 5,734.00 monthly) is estimated, considering a production of 8,256 bags of 45 kg c / u expected. It is concluded that due to the high profitability, this is 193%, an IRR and positive NPV, added that a B / C of 1.93 feasibility of creating a company that takes advantage of organic waste to